2021
DOI: 10.21203/rs.3.rs-1071359/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential Nitrate Reduction Rates in Marine Mangrove Sediments in the Lesser Antilles

Abstract: Mangrove sediments are generally nitrogen limited, with nitrate reduction to ammonium instead of denitrification in these sediments, resulting in nitrogen retention rather than nitrogen elimination. The goal of this work was to investigate the potential for nitrate reduction in marine mangrove sediments along a canal impacted by anthropogenic activity (Guadeloupe, West Indies) as a function of increased nitrogen load and how this would change nitrate transformation rates. In addition to that, the impact of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…This showed that the growth of mangrove vegetation cannot be optimal if the nitrate level in the waters is too high. Nitrogen is a nutrient for the growth and development of aquatic organisms (Laverman et al 2021).…”
Section: Correlation Between Water Quality Macrozoobenthos Community ...mentioning
confidence: 99%
“…This showed that the growth of mangrove vegetation cannot be optimal if the nitrate level in the waters is too high. Nitrogen is a nutrient for the growth and development of aquatic organisms (Laverman et al 2021).…”
Section: Correlation Between Water Quality Macrozoobenthos Community ...mentioning
confidence: 99%